Peningkatan Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Discovery Learning - Ridwan, Siti Luthfah (Jurnal Didaktika Pendidikan Dasar, 2021)
Meaningful learning is learning that takes the side of students and makes students as the main actors who are active with their friends identifying problems, looking for solutions and concluding and actively communicating in learning activities. Activities like this can be done by implementing the Discovery Learning model. The purpose of this study was to improve critical thinking skills and student learning outcomes in the classification of living things. This research is a Classroom Action Research model of Kemmis and Taggart through four stages, namely planning, implementing, observing, and reflecting which were carried out in two cycles and each cycle carried out three meetings. The results of the data analysis showed that the percentage of students who achieved the critical thinking indicator was 14 students (56.00%), 17 students (68.00%) who achieved the knowledge competency learning outcomes. Whereas in Cycle 2, there were 22 students (88.00%) who reached the critical thinking ability indicator, and 21 students (84.00%) who reached the learning outcome indicator. From the results of these studies it can be concluded that the Discovery Learning learning model can improve critical thinking skills and learning outcomes of students.